2020
DOI: 10.1530/ec-20-0206
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and PTH: data from a cross-sectional study in an equatorial population

Abstract: Objective: Investigate the prevalence of vitamin D deficiency in an equatorial population through a large-sample study. Methods: Cross-sectional study with 30,224 healthy individuals from the North Region, in Brazil (Amazônia, state of Pará), who had 25-hydroxy-vitamin D (25(OH)D) and intact parathyroid hormone (PTH) serum levels measured by immunoassay method. Those with history of acute or chronic diseases were excluded. Abnormal levels of calcium, creatinine, glycemia and albumin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
(60 reference statements)
1
2
0
Order By: Relevance
“…However, Salvador, a city located in the northeast of Brazil, had a percentage of vitamin D deficiency or insufficiency very close to Curitiba in the south region. This was demonstrated before in other tropical cities of the north and northeast of Brazil in specific populations of postmenopausal women and older individuals, but for the first time in a healthy population ( 16 , 17 ). Although Salvador has a higher percentage of dark-skinned individuals than Curitiba, these cities had averages of 25(OH)D that were not different from each other.…”
Section: Discussionsupporting
confidence: 66%
“…However, Salvador, a city located in the northeast of Brazil, had a percentage of vitamin D deficiency or insufficiency very close to Curitiba in the south region. This was demonstrated before in other tropical cities of the north and northeast of Brazil in specific populations of postmenopausal women and older individuals, but for the first time in a healthy population ( 16 , 17 ). Although Salvador has a higher percentage of dark-skinned individuals than Curitiba, these cities had averages of 25(OH)D that were not different from each other.…”
Section: Discussionsupporting
confidence: 66%
“…Additionally, another research revealed that there is a drop in blood 25(OH)D concentrations when body mass index (BMI) increases. This suggests that there is a correlation between low vitamin D levels and obesity [31] . Some of the proposed mechanisms that might explain this phenomenon include reduced exposure to sunlight, changes in the activation of vitamin D, and an increase in the storage of vitamin D in adipose tissue [18,32,33] .…”
Section: Discussionmentioning
confidence: 98%
“…The covariates included in the regression model from [31] had little predictive power, as they were only able to account for 5.4% of the variance in 25(OH)D levels. Exploring the impact of genetic variations on the functioning of the vitamin D receptor (VDR) is an important hypothesis that might provide insights into these findings.…”
Section: Discussionmentioning
confidence: 99%
“…They have not evaluated DKD. The present study used the large VIDAMAZON database (19), being, as we are aware, the first population-based study to establish the association of higher VD levels with better glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…The present study used the large VIDAMAZON database, which includes data from over 30,000 individuals and has already provided evidence on other VD aspects (19). We included 1,576 diabetic patients who had their diagnosis confirmed by laboratory data and medical history, but we had no access to their medical records and our laboratory data did not contain antibodies related to type 1 DM and C-peptide.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%